(3OQGSI JMdjdjI JCUjdjI eRhOI h eOYeI HGdGLfOGJ GdbVGFjIs - (3YGeQ eMehO(B, (3GdcShGfjs ((3YeGf(B:s (3OGQ GdKbGaI(B,s, 2010)
(3GdfTCI GdJGQjNjI ddYdGeI GdJLGQjI , CgejI, hXjaI h TQhW GdYdGeI GdJLGQjI , JYQja GdYdGeI GdJLGQjI , GdYdGeI GdJLGQjI hHGbj eaQOGJ GdedcjI GdacQjI , GdLQGFe GdeYdheGJjI , XGgQI JRhjQ GdYdGeI GdJLGQjI , GdQcf GdeGOj ddJRhjQ h eOi EfWHGbg Ydi GdJRhjQ GdeYdheGJj , GdQcf GdeYfhj dLQjeI JRhjQ GdYdGeI GdJLGQjI h eOi GfWHGbg Ydi GdJRhjQ GdeYdheGJj , YbhHI LQjeI JRhjQ GdYdGeI GdJLGQjI , LQjeI GSJYeGd GdYdGeI GdJLGdQjI GdeRhQI eYdheGJjGs
(3eQGLY U(B.237s
Keywords: (3GdCSeGA GdJLGQjIs; (3GdJRhjQs; (3GdYdGeGJ GdJLGQjIs